Uso e seleção de hábitat de nidificação e identificação dos fatores de influência no sucesso dos ninhos de Elaenia chiriquensis (Aves: Tyrannidae) em área de Cerrado na Estação Ecológica de Itirapina, região central do estado de São Paulo - Silva, Marina Telles Marques da (Universidade Federal de São Carlos, 2012)
Nesting is a critical step on bird s life cycle, since nest predation is high all over the world. Predation influences the population dynamics, the community structure and the life history of birds. Birds evolved anti-predatory strategies, which include selection of safer places for nesting. Here we intent to: (i) analyze habitat characteristics selected by adults, and (ii) evaluate the influence of these elements on nests success, and fitness consequences to individuals. We studied the Lesser Elaenia (Elaenia chiriquensis), a migratory bird that breeds in Brazilian Savannas. We conducted the study between 2010 e 2011 in a 100 ha area in the Estação Ecológica de Itirapina, a protected area in São Paulo state, were the Lesser Elaenia is abundant along its breeding season (September to December). We analyzed habitat selection comparing characteristics of used and available patches. We made all tests using chi-square tests, analysis of variance, paired t-tests and permutation tests. We used program MARK to evaluate the influence of all of the parameters on nests success. We created a set of models that included temporal and a set of environmental parameters and used Akaike s Information Criterion to evaluate the adjustment of each model to our data. Adults apparently selected anemochoric plants, with larger crowns and more lichen flakes on stalks, but did not show preference for specific plant species. Individuals also preferred patches with high plant density and high density of Aspidosperma tomentosum, the most used plant as nest substrate. Contrary of our expectations, none of these characteristics influenced nests success. However, some parameters not evaluated for selection, influenced the offspring survival. Vegetation density on nest sites was the most important variable, probably because it helps concealing nests and parental activities. Nest age and time along the breeding season were also important elements and both reduced nests success. Nest predation, habitat selection, and their consequences to the fitness are complex and are related to many variables. The present study contributed with the knowledge on this subject in tropical areas.
Keywords: Ecologia da população; Cerrados; Predação de ninhos; Historia natural; Ecologia de comunidades; Elaenia chiriquensis; Seleção de hábitat de nidificação; Sucesso dos ninhos; Brazilian Savanna, Lesser Elaenia; Nest predation; Nest site selection; Nest success; CIENCIAS BIOLOGICAS::ECOLOGIA